The role of knowledge management on learning organization capacity and job performance - Nurhayati, Tatiek; Pitaloka, Wulandari Dyah (Library of Sultan Agung Islamic University, 2022)
In the digital era, knowledge becomes the main asset to win the competition. However, the management of knowledge that is less than optimal makes the targets set by the company's management cannot be achieved. This indicates that HR performance in utilizing Knowledge Management is still not optimal. This study aims to examine and analyze the influence of Tacit Knowledge and Explicit Knowledge on Job Performance through Learning Organization Capacity. The population in this study is a building material manufacturing company in Central Java, with a sample of 100 respondents. The sampling technique used in this study was purposive sampling and data analysis used PLS. The results showed that Tacit Knowledge and Explicit Knowledge had a positive effect on Learning Organization Capacity and also, Knowledge Management and Learning Organization Capacity had a positive effect on Job Performance.